The role of human development in achieving sustainable development - Arif, Moein Thabit; Saeed, Hashem Mohammad (Journal of University of Human Development, 2016)
There are several problems of developing countries and distributed causes between physical and administrative , planning, and procedural and legislative , and reference these problems but spin by Ray researcher on human resources that are planned and port , decision maker, it has become these problems sustained and added to it the problem of sustainable environment to add dimension requires policy-making for designs according to need for developing community to prepare human cadres specifications according to the capacity of the community to achieve sustainable development, which is now the other one of the exits of the developing countries of their problems and that of the most prominent legibility of environmental degradation , either through use and consumption pattern of industry and even living, which requires human skills and extensive influence in bringing about change in the course of these facts toward effective solutions , therefore, to address this topic in the forums scientific and practical is important to start a phase change seriously to and an open mind to accept and taking the experiences of countries that have preceded us in this area , targeting the development of possible scenarios and applicable in the reality of these countries and commensurate with the resources and capability to at the current stage of implementation or the future.